Assessing Listening Skills Through Student Interest on Narrative Text Based ISL Collective Video Quizzes at Course - Riska Ayunda; Meisuri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
Listening comprehension is often overshadowed by reading- and writing-centered instruction in junior high English classes, limiting opportunities for learners to develop real-world communication skills. Addressing this gap, the present qualitative study explores how narrative text–based internet second-language collective video quizzes shape student interest and, in turn, enhance listening assessment. Guided by Krapp’s Person-Object Theory of Interest, the research examined 20 Indonesian junior teenagers enrolled in an extracurricular conversation course. Data were gathered through a structured questionnaire and follow-up semi-structured interviews with five focal students. Questionnaire items were mapped onto the emotional, value-related, and cognitive dimensions of interest, while interview transcripts provided nuanced insight into learners’ experiences. Findings reveal robust engagement across all three dimensions: 85 % of students reported positive emotions such as enjoyment and excitement, 80 % perceived the activity as personally valuable for real-life English use, and 90 % demonstrated heightened cognitive involvement, including curiosity, prediction, and vocabulary acquisition. Interview data corroborated these patterns, highlighting the motivational power of storylines, visual cues, and immediate feedback embedded in the quizzes. Collectively, the results indicate that narrative video quizzes are not merely attractive add-ons but effective, interest-driven tools for assessing and fostering listening skills in adolescent EFL contexts. The study recommends integrating similar multimedia, story-rich assessments to create learner-centered, low-anxiety listening environments. Keywords: listening assessment student interest narrative text ISL Collective Video Quizzes